Challenging the “Neutrality” of Public Service in the 1960s: The Wednesday Plays of Tony Garnett and Ken Loach - Susannah O’Carroll (Revue Française de Civilisation Britannique)
Starting from the question of the BBC’s supposed social and political neutrality, the article examines a specific moment in the history of the Corporation, the 1960s, by focusing on an innovation in television production: a series of single plays (television dramas) called The Wednesday Play. The article examines the institutional origins of the series in relation to a critical assessment of the BBC in the Pilkington Report of 1962 and the subsequent broadening of the social origins of recruits in anticipation of the second public-service channel, BBC2. The article goes on to consider three emblematic plays, in order to illustrate both the potentialities and the problematic issues arising from mixing fictionality and veracity. Finally, the lasting social and political significance of these plays is assessed as a unique moment in the history of the BBC.